An Ayurgenomics Approach: Prakriti-Based Drug Discovery and Development for Personalized Care - Huang, Zoufang; Chavda, Vivek P.; Bezbaruah, Rajashri; Uversky, Vladimir N.; P., Sucharitha; Patel, Aayushi B.; Chen, Zhe-Sheng (Frontiers in Pharmacology, 2022)
Originating in ancient India, Ayurveda is an alternative medicinal approach that provides substantial evidence for a theoretical-level analysis of all aspects of life. Unlike modern medicine, Ayurveda is based upon tridoshas (vata, pitta, and kapha) and prakriti. On the other hand, the research of all the genes involved at the proteomics, metabolomics, and transcriptome levels are referred to as genomics. Geoclimatic regions (deshanupatini), familial characteristics (kulanupatini), and ethnicity (jatiprasakta) have all been shown to affect phenotypic variability. The combination of these two streams, genomics, and Ayurveda provided new insights into investigation and, as a result, paved the way for precision medicine known as ayurgenomics. Through successful coordination of 'omics,' prakriti-based treatments can help change the existing situation in health care. Ayurvedic methodologies are based on three prakriti aspects: aushadhi (medication), vihara (lifestyle), and ahara (diet). A foundation of prakriti-based medicine, preventative medicine, and improvement of life quality with longevity can be accomplished through these ayurvedic characteristics. In this perspective, we try to understand prakriti’s use in personalized medicine, as well as how to integrate it with programs for drug development and discovery.